(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Big Data Analytics has its importance in almost all the real time applications ranging from Science & Technology to Market Prediction to Weather forecasting and many more. One such important area where analytics played a crucial role is Agriculture. Understanding the previously available agricultural data and studying the underlying pattern can help in making accurate future predictions. A well-known fact that the majority of population (≥55%) in India is into agriculture, the analytics and prediction can be really useful to them. Various factors are to be considered which have direct impact on the production of the crops. The use of technology in agriculture has increased in recent year and data analytics is one such trend that has penetrated into the agriculture field. In this paper, the data of Government Crop Production is analyzed on various parameters which will help in predicting the Crop Yield.